Acceptance procedure for the linear accelerator component of the 1.5 T MRI‐linac. Issue 8 (17th July 2021) - Woodings, Simon J.; de Vries, J. H. Wilfred; Kok, Jan M. G.; Hackett, Sara L.; van Asselen, Bram; Bluemink, Johanna J.; van Zijp, Helena M.; van Soest, Theo L.; Roberts, David A.; Lagendijk, Jan J. W.; Raaymakers, Bas W.; Wolthaus, Jochem W. H.
Abstract: Purpose: To develop and implement an acceptance procedure for the new Elekta Unity 1.5 T MRI‐linac. Methods: Tests were adopted and, where necessary adapted, from AAPM TG106 and TG142, IEC 60976 and NCS 9 and NCS 22 guidelines. Adaptations were necessary because of the atypical maximum field size (57.4 × 22 cm), FFF beam, the non‐rotating collimator, the absence of a light field, the presence of the 1.5 T magnetic field, restricted access to equipment within the bore, fixed vertical and lateral table position, and the need for MR image to MV treatment alignment. The performance specifications were set for stereotactic body radiotherapy (SBRT). Results: The new procedure was performed similarly to that of a conventional kilovoltage x‐ray (kV) image guided radiation therapy (IGRT) linac. Results were acquired for the first Unity system. Conclusions: A comprehensive set of tests was developed, described and implemented for the MRI‐linac. The MRI‐linac met safety requirements for patients and operators. The system delivered radiation very accurately with, for example a gantry rotation locus of isocenter of radius 0.38 mm and an average MLC absolute positional error of 0.29 mm, consistent with use for SBRT. Specifications for clinical introduction were met.